ENTREPRENEURSHIP BEHAVIOR OF CHINESE COMMUNITIES IN SUMEDANG DISTRICT OF SUMEDANG, WEST JAVA. - CHOTIM, ENDAH RATNAWATY (Human Sustainability Procedia, 2018)
This research is about entrepreneurship behavior of Chinese communities in Sumedang District of Sumedang, West Java. The Chinese communities arewell-known to have good spirit ofentrepreneurship. This can be seen from their success not only in controlling Indonesian economy, but also Asian and even the world economy. The Chinesecommunitiesin Sumedang have also been successful and have been survived better than other ethnicities. The difference between the Chinese and other ethnicities is on the Chinese ability in managing their business professionally, accountability, the separation between personal wealth from their business asset and forming of cadres from the early age of their children. Their religion and tradition have also supported the success of the Chinese to compete with other ethnicities